State of mind - Ng, Jacelyn Jie Ling (Nanyang Technological University, 2020)
Our mind is the universal basis of all experiences; happiness, suffering, life and death. It guides and shapes the things we do, as well as how we perceive the world. State of Mind is an immersive spatial installation that materialises the core of our mind, where the viewer goes through a journey of seeking an anchor in a land of barrenness, and inevitably, contemplating on their inner self and the perceived reality. The work hopes that the experience becomes a form of reminder to one, that no matter what wind or storms may come, your anchor will always be there for you to return back to.